Presence of Fatty Liver and the Relationship between Alcohol Consumption and Markers of Inflammation - Martin Kächele; Stefan Wolff; Wolfgang Kratzer; Mark Haenle; Jörg Homann; Gerlinde Trischler; Wolfgang Koenig; Armin Imhof (Mediators of Inflammation)
Background and Aims. Local and systemic inflammation represent a major feature of atherosclerotic cardiovascular disease (CVD) and are also linked to nonalcoholic fatty liver disease (NAFLD). Studies indicate that NAFLD might be a risk factor for CVD whereas low-to-moderate alcohol consumption is associated with lower cardiovascular morbidity and mortality compared to abstainers and heavy drinkers. We hypothesize that FLD interacts with the effect of alcohol intake on markers of inflammation, and thus potentially on cardiovascular risk. Methods and Results. We evaluated alcohol consumption, markers of inflammation and sonographic criteria of FLD in 515 subjects, representing a subsample of a cross-sectional population based study (Echinococcus multilocularis and Internal Diseases in Leutkirch (EMIL) Study). Presence of FLD was markedly reduced in subjects drinking 0–20 g alcohol/d (19%), compared to nondrinkers (35%) and heavy drinkers (34–44.9%). Serum concentrations of inflammatory markers were substantially higher in subjects with FLD. However, presence of FLD showed no effect on the association between alcohol consumption and inflammatory biomarkers. Conclusions. Based on data from a population-based sample, there is no evidence for a link between FLD, alcohol consumption, and inflammatory cardiovascular risk markers. However, larger prospective studies are needed to confirm this.